The Impact of Corporate Governance on Changing Financial Performances of Mergers and Acquisitions: Examining the Relationship between Corporate Governance and Financial Performances in Indian Mergers and Acquisitions (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In  the  present paper,  we  construct  a  corporate  governance index  for  a  sample of  93  Indian companies  listed on  Bombay Stock Exchange  and National  Stock Exchange.  The index  is based  on a comprehensive  set  of 64  governance attributes  for these  sample  companies, the  companies, then,  have been  classified into  four governance  portfolios  using their  corporategovernance  ranking.  Furthermore, we  have calculated  average  of 3 years  post - mergers  and acquisitions  (M&A)  financialperformance  and  valuation ratios  for each  governance portfolio.   Our findings  suggest good  governance appears  to be  ofmuch  value  as we  found significant  higher  post mergers  and acquisitions  rate  of return  ratios for  companies in  top quartiles. We  also report significant  higher valuation ratios for companies  in top  governance portfolio. The present  study  concludesthat  companies  with  higher  rank  for  corporate  governance  score  are  good  performers  which  are  revealed from  better financial ratios. Their  post M&A  better financial  performance and  valuation shows  that good  governed companies  bring positive  synergies from  their M&  A  activities which  is recognized  by market  reflected in  higher valuation  ratios.